Learning Cycle-Inquiry Effect on Pre-Service Elementary Teachers’ Science Process Skills and Content Knowledge - Yanti, Yulia Eka; Susilo, Herawati (Pedagogika, 2023)
This study explored the effects of Learning Cycle and Inquiry (LCI) on pre-service teachers’ science process skills (SPS) and concept knowledge (CK). The experimental group was taught using the LCI. The positive control group 1 learned using the inquiry, the positive control group 2 learned using the learning cycle-5E, and the negative control group was involved in conventional learning processes. The study results revealed significant differences in the research participants’ CK and SPS.